Menciptakan Ide Kreatif - Erwan Efendi; Cindy Suci Aisyah Simarmata; Rizky Fadli Harahap (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The goal of this study is to help students come up with original ideas for da'wah activities. This will make the teaching more engaging, preventing students from becoming bored and making it easier for them to comprehend the material. Because da'wah must be adapted to the conditions of their mad'u, a Da'i and Da'iyah must be able to come up with good creative ideas by always paying attention to the people they face (the congregation). Therefore, preaching to parents, youth, and children ought to be different. This takes into account the mad'u's intelligence and challenges. This study employs descriptive qualitative analysis, which places a greater emphasis on in-person interviews and in-the-moment field observations to better comprehend the perfect conditions for the subjects under investigation. Fundamentally, in teaching we will be more compelling and not exhausting. We must have creative ideas and consider how the delivered da'wah can be accepted and understood by the mad'u when we deliver da'wah materials. Keywords: Da'wah, Creating Ideas, Creative.